Caroço de algodão e glicerina bruta em suplementos múltiplos na terminação de bovinos à pasto - Possamai, Adriano Jorge (2014)
Objective was to evaluate the association of whole cottonseed and crude glycerin in multiple supplements for cattle in the finishing phase in the rainy season on dry matter intake, nutrient digestibility, carcass characteristics, lipid profile of meat produced, growth performance and economical. Two experiments were conducted to evaluate the association of two levels of cottonseed (0 and 25%) and two levels of crude glycerin (0 and 15%) in multiple supplements, supplying 4 kg/animal/day equivalent offer to 0 75% of the average body weight of animals. The first experiment was used five Nellore steers with the end of 649.5±40.47 kg, distributed in 5x5 Latin square design for the intake and digestibility trials starting weight of 546.5±29.35 kg for and comparing with the offer mineral supplementation. Supplementation increased the total dry matter intake (P=0.037), ether extract (P<0.001), crude protein (P<0.001), non-fiber carbohydrates (P<0.001), dry matter digestibility (P<0.001), ether extract (P< 0.001) and crude protein (P<0.001). Experiment 2 evaluated the association of these ingredients on performance and carcass traits using 40 Nellore steers with an initial weight of 472±23.23 kg. There was no influence of supplementation indicating that the nutrient intake was maintained regardless of the formulation used, reaching final weight, average daily gain, final subcutaneous fat thickness and hot carcass yield of 586.9±33.15 kg±1.35 0 23 kg/day, 5.89±0.80 mm and 56.25±1.6%, respectively. A reduction in the content of short-chain fatty acids by using cotton seed, increased as the glycerin content of C18: 2 c9 t11 (CLA) (P=0.046) acid important for reducing serum cholesterol consumers. Up to 25% of cottonseed and 15% crude glycerin can be used in multiple supplements for cattle on pasture without damages to ruminal fermentation, growth performance or carcass characteristics, and you can also manipulate the lipid profile of meat produced. The economic evaluation considered the elevation of slaughter weight and use of alternative formulations The increase in slaughter weight was favorable economically, with rate of return on capital of 2.47% per month, considering the average the formulations, although the higher profitability has been attained by providing CAGLIC supplement (2.64% per month) given the lower cost of the supplement and maintenance performance. The minimum average daily gain for profitability equal to the savings account was 1.04 kg/animal/day, showing good safety margin on investment. However, the income can vary with the price of ingredients standards. In scenarios high prices of the ingredients of the return patterns using alternative ingredients may be up to 40% higher than using the standard formulation. Thus one should consider the prices of the ingredients for making a decision on the formulation of multiple supplements for finishing cattle termination to pasture in the rainy season.